DETERMINAN KUALITAS AUDIT MENURUT TEORI ATRIBUSI - Santosa, R. Ery Wibowo A; Kristiana, Ida; Faturochmah, Sendifida (Politeknik Negeri Semarang, 2024)
This study aims to empirically prove the effect of Independence, Due Professional Care, and Time Budget Pressure on Audit Quality and work experience. The number of samples used in this study was 64 auditors from 13 Public Accounting Firms in Semarang City. Sampling in this study was carried out using the purposive sampling technique, namely determining the sample by taking samples from the population based on specific criteria. This research uses quantitative data analysis techniques and data analysis methods with Partial Least Square (PLS) approach using WarpPLS 7.0 software. The analysis technique used is the outer model and the inner model. The results of this study indicate that independence has a positive effect on audit quality, due professional care has a positive impact on quality, time budget pressure has a negative effect on audit quality, and work experience does not affect audit quality.